694Metabolic conditions have high prevalence in CHamoru men in a hyperuricemia feasibility study in Guam. (2nd September 2021) - Paulino, Yvette C.; Camacho, Frank; Merriman, Tony; Matisoo-Smith, Lisa; Paulino, Tristan; Chennaux, Jade SN; Mori, Elua; Gosling, Anna L.
Abstract: Background: One-third of adults in the U.S. have metabolic syndrome, a combination of risk factors of chronic diseases such as heart disease, kidney disease, diabetes, and gout. These diseases are a burden for ethnic minorities, including Pacific Island peoples. Here, the metabolic conditions were described for a group of Pacific Island people, the CHamorus or natives of Guam, a U.S. Territory in the Mariana Islands in the Western Pacific. Methods: A cross-sectional survey was conducted in Guam from August 2019 to January 2020. A non-random sample of 152 adults, ≥18 years old, with CHamoru ancestry were recruited and consented. Information collected included socio-demographics, metabolic history, lifestyle behaviors, height and weight, blood pressure, and non-fasting blood and urine. Statistical analyses included frequencies of metabolic conditions and Pearson's Chi-square test for gender differences, alpha=0.05. Results: Of the 152 CHamorus, 49.3% were male, 50% were female, and 0.7% was transgender. The mean age was 43±15.1 years. Mean education was 14.4±3.6 years and hyperuricemia he majority (69.7%) pursued postsecondary studies. Self-reported metabolic conditions included: diabetes (19.7%), gout (28.9%), hypertension (34.9%), dyslipidemia (17.8%), and heart conditions (9.9%). Compared to females, more males reported gout (40.5% versus 18.7%; P=.003) and measured to be hypertensive (48% versus 21.1%; P<.0001), hyperuricemic (58.9% versus 31.6%; P=.001), and obese (77.3% versus 46.1%; P<.0001). Conclusion: Metabolic conditions were common among CHamorus, though gout, hypertension, hyperuricemia, and obesity were predominant in the men. Key messages: Strategies to reduce the burden of metabolic conditions may be targeted to CHamoru men in this community.